Frontline services of the Provincial Environment and Natural Resources Office, La Union - Flores, Krizia Marie C. (City of San Fernando, La Union : [s.n.], 2017)
This descriptive study assessed the frontline services of the Provincial Environment and Natural Resources Office, La Union. Specifically, it looked into the level of satisfaction of the clients on the frontline service along the application for free patent, issuance of survey authority, issuance of certificate of tree plantation and ownership, issuance of certficate of verification, and application for chainsaw registration; the strengths and weaknesses; and the problems encountered on the frontline services. Data gathered were treated using frequencies, weightd mean, ranking and percentage. A total of 197 walk-in clients participated in the study.
Bibliography: pages 74-78.
CHED-La Union
Keywords: Personnel management